2018
DOI: 10.1002/wene.289
|View full text |Cite
|
Sign up to set email alerts
|

Technical and social problems of nuclear waste

Abstract: Despite decades of effort, the nuclear industry does not yet have a working solution for managing spent fuel and high level waste, the most radioactive products generated by nuclear power plants. Although many scientific and technical bodies have endorsed geological disposal as the preferred solution to this problem, there remain significant uncertainties about the long-term performance of repositories and behavior of the nuclear wastes to be stored in these facilities. Apart from a minority of countries, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…However, nuclear power is highly contentious amongst members of the public [36]. Intense controversies often develop around the siting of new nuclear facilities and waste repositories [37] as well as the environmental and public health risks borne by uranium mining and milling communities [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, nuclear power is highly contentious amongst members of the public [36]. Intense controversies often develop around the siting of new nuclear facilities and waste repositories [37] as well as the environmental and public health risks borne by uranium mining and milling communities [38].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have indeed documented in other countries, the importance of public acceptance of nuclear power technology for its successful development as cleaner alternative and part of a nation's energy mix (Yoshida, 2015;Ramana, 2018;Fan, 2018;Wang et al, 2019). In the case of the UAE, we found that increased interest in ecosystem services and sustainability among present day adolescents leads to more awareness of, while conjointly reducing optimism towards the use of nuclear electrical power technology in the country.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 54%
“…According to Figure 19, starting in 2040, the PWR nuclear power plants will notably reduce their electrical capacity. This situation is likely to influence decisions about future investment and operating costs [71], as well as prospects for the decommissioning and management of high-level radioactive waste at current nuclear power plants [72][73][74][75][76][77]. Lastly, if no advances are made in R&D of new designs or in the use of the actual nuclear power plants in cogeneration systems for the production of hydrogen [78,79], in 2050 this technology will decrease its generation capacity to 50%, keeping 127 GWe and the number of operating rectors at 70%.…”
Section: Simulation Of the Life Extension Of Operational Pwrmentioning
confidence: 99%